Evaluation of density, volume, height and rate of bone resorption of substitutes of autologous bone grafts for the repair of alveolar clefts in humans: a systematic review (2020)
Objective: To assess clinical studies that compare synthetic or enriched natural materials to autologous osseous grafts among individuals with cleft lip and palate to determine which would be the substitute to autologous bone graft for alveolar cleft repair in humans. Materials and methods: Randomized and controlled clinical trials on alveolar clefts treated with synthetic bone substitutes and autogenous bone grafts combined with osteoinductive factors compared with autogenous bone grafts alone (with ≥4-month follow-up and reporting clinical/radiographic data) were considered eligible. MEDLINE, EMBASE, and Central databases were searched for articles published until February 2020. Results: Of 73 eligible articles, 15 were included. Some inductive factors along with iliac crest bone decreased bone reabsorption, preserved the generated bone height/width, and reduced the required autologous bone graft volume. Bone morphogenetic protein (BMP2) as an autologous bone graft substitute, demonstrated satisfactory alveolar defect healing, by avoiding autograft use. Many materials did not yield better outcomes than did autologous grafts; however, hydroxyapatite and collagen complex, hydroxyapatite agarose composite gel, acellular dermal matrix film, fibrin glue, platelet-rich plasma, and deproteinized bovine bone showed similar bone healing outcomes, being an alternative alveolar defect treatment. Conclusions: BMP2, as an osteoinductive factor along with a synthetic matrix, yields satisfactory bone healing and avoids the need for autologous bone grafts. However, high-quality RCTs are necessary to determine the most effective and safe concentration and protocol of BMP2 utilization as a substitute for the autologous iliac crest bone grafting.